The Impact of Energy Use in Agriculture and Manufacturing Value Added in Sri Lanka - Selvamalai, T. (University of Jaffna, 2016)
The study investigates the impact of energy use on agriculture and manufacturing value added in Sri Lanka between 1971 and 2011. The study used only three variables, energy use (Kg of Oil equivalent), agricultural value added (constant 2010 US$), and manufacturing value added (constant 2010 US$). The data was gathered from the database of World Bank. The study has applied times series econometrics techniques, especially cointegration and Granger causality test. The study founds several results. In Sri Lanka, there was no long-run equilibrium relationship between energy use, agricultural value added, and manufacturing value added. And there was a bivariate causal relationship between energy use and manufacturing value added while there was no causal relationship between energy use and agricultural value added at 5% significant level.
Keywords: Agriculture; Cointegration; Energy use; Granger causality; Manufacture; Value added